PENGARUH MOTIVASI TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA KOPERASI PEMBIAYAAN SYARIAH (KSPP) OKU TIMUR - Muhammad Nuh Hudawi (STIE Trisna Negara OKU Timur, 2020)
Work effectiveness is a measure and the ability to carry out the functions, tasks, programs, or missions of an organization or company according to predetermined targets (quantity, quality, and time). To find out the influence of motivation and work effectiveness at the East OKU Belitang Islamic Financing Cooperative (KSPPS), a study was conducted and obtained the results of the correlation data between motivation and work effectiveness of employees, it can be obtained the number 0.528 and the percentage level = 27.8%. So to answer the hypothesis that has been proposed previously, namely the Effect of Motivation and Work Effectiveness of Employees in the Belitang OKU Timur Sharia Financing Cooperative (KSPPS) is not proven. To answer the hypothesis that has been put forward using the hypothesis test formula, obtained (t) table = 1,860, while (t) arithmetic = 1.752 which can be concluded that (t) arithmetic <(t) table or (t count is smaller than t table) so that the hypothesis proposed in the previous chapter is not proven, because the correlation is moderate.